The role of protein Z and protein Z-dependent protease inhibitor polymorphisms in the development of prosthetic heart valve thrombosis - Karakoyun, Süleyman; Gürsoy, Mustafa Ozan; Kalçık, Macit; Yesin, Mahmut; Gündüz, Sabahattin; Astarcıoğlu, Mehmet Ali; Bayram, Zübeyde; Çakal, Beytullah; Bayam, Emrah; Özkan, Mehmet (My University, 2017)
BACKGROUND AND AIM OF THE STUDY: Protein Z (PZ) is a vitamin K-dependent factor that is synthesized mainly by the liver. It acts as an activator of serpin, the protein Z-dependent inhibitor (ZPI), which inhibits factor Xa. The potential role of alterations in protein Z and/or ZPI levels in the pathogenesis of thrombotic and/or hemorrhagic diseases has been previously investigated, but results have been conflicting. The study aim was to evaluate the role of PZ/ZPI polymorphisms in the development of prosthetic valve thrombosis (PVT).METHODS: This prospective, observational cross-sectional study included 50 consecutive patients with PVT [non-obstructive thrombosis (NOT) in 35 patients; obstructive thrombosis (OT) in 15] and 50 consecutive healthy subjects with normally functioning prostheses. gDNA was extracted from ca. 5 × 106 leukocytes, using the QIAamp DNA Mini Kit (Qiagen), according to the manufacturer's recommendations. For mutational analysis, a minisequencing method was employed. Results of the analyses were compared between the PVT and control groups, and also between the OT and NOT subgroups.RESULTS: The frequency of A allele (mutant type) of PZG79A was equal in all PVT patients and in controls. With regards to PZ-A13G polymorphisms, frequency of the mutant G allele was 22% in PVT patients and 19% in controls. Serpina-R67X polymorphism was observed in 8% of PVT patients and 6% of controls. Normal variant CC was present in 47 controls (94%), whereas a heterozygotic mutation (CT) was detected in four PVT patients (8%). Frequency of the ZPI-R67X mutation was significantly higher in patients with OT than in those with NOT (p = 0.041).CONCLUSIONS: The present study was the first to evaluate the potential impact of PZ (PZ-A13G, PZG79A) and ZPI (R-67X, W303X) polymorphisms in the development of PVT. Based on the results of this small observational case-control study, PZ/ZPI polymorphisms do not appear to play an active role in the development of PVT. Hence, further extensive studies are necessary.
Keywords: Prosthetic Heart Valve Thrombosis; Protein Z; Dependent Protease Inhibitor Polymorphisms